Justified ethicality: Observing desired counterfactuals modifies ethical perceptions and behavior - Shalvi, Shaul; Dana, Jason; Handgraaf, Michel J.J.; De Dreu, Carsten K.W. (Organizational behavior and human decision processes, 2011)
Employing a die-under-cup paradigm, we study the extent to which people lie when it is transparently clear they cannot be caught. We asked participants to report the outcome of a private die roll and gain money according to their reports. Results suggest that the degree of lying depends on the extent to which self-justifications are available. Specifically, when people are allowed to roll the die three times to ensure its legitimacy, but only the first roll is supposed to “count,” we find evidence that the highest outcome of the three rolls is reported. Eliminating the ability to observe more than one roll reduces lying. Additional results suggest that observing desired counterfactuals, in the form of additional rolls not meant to determine pay, attenuates the degree to which people perceive lies as unethical. People seem to derive value from self-justifications allowing them to lie for money while feeling honest.